Differential arterial and venous endothelial redox responses to oxidative stress. (23rd July 2018) - Shrestha, Bandana; Prasai, Priya K.; Kaskas, Amir M.; Khanna, Ankur; Letchuman, Vijay; Letchuman, Sunjay; Alexander, Jonathan Steven; Orr, A. Wayne; Woolard, Matthew D.; Pattillo, Christopher B.
Abstract: Objective: Oxidative stress is a central event linked with endothelial dysfunction and inflammation in several vascular pathologies, marked by over‐production of ROS and concomitant decreases in antioxidants, for example GSH. Here, we distinguish endothelial oxidative stress regulation and associated functional disparities in the two main vascular conduits, (arteries and veins) following decreases in GSH. Methods: MAECs and VCECs were used as models of arterial and venular endothelium, respectively, and BSO (0‐100 μmol/L) was used to indirectly increase cellular oxidative stress. Inflammatory responses were measured using immune cell attachment and immunoblotting for endothelial cell adhesion molecule (ICAM‐1, VCAM‐1) expression, altered cell proliferation, and wound healing. Results: MAECs and VCECs exhibited differential responses to oxidative stress produced by GSH depletion with VCECs exhibiting greater sensitivity to oxidative stress. Compared to MAECs, VCECs showed a significantly increased inflammatory profile and a decreased proliferative phenotype in response to decreases in GSH levels. Conclusions: Arterial and venous endothelial cells exhibit differential responses to oxidant stress, and decreases in GSH:GSSG are more exacerbated in venous endothelial cells. Specific pathogenesis in these vascular conduits, with respect to oxidant stress handling, warrants further study, especially considering surgical interventions such as Coronary artery bypass grafting that use both interchangeably.